Letter from Carl P. Miller to members of the Los Angeles business community - Miller, Carl P. (1955)
This letter from then LA Chamber of Commerce president Carl Miller asks Los Angeles business and industry leaders to collaborate to fight smog.
Keywords: California--Los Angeles; Smog; Air--Pollution